Two putative acetyltransferases, san and deco, are required for establishing sister chromatid cohesion in Drosophila. - Williams, B.C.; Garrett-Engele, C.M.; Li, Z.; Williams, E.V.; Rosenman, E.D.; Goldberg, M.L. (Current Biology, 2003)
Sister chromatid cohesion is needed for proper alignment and segregation of chromosomes during cell division. Chromatids are linked by the multiprotein cohesin complex, which binds to DNA during G(1) and then establishes cohesion during S phase DNA replication. However, many aspects of the mechanisms that establish and maintain cohesion during mitosis remain unclear.We found that mutations in two evolutionarily conserved Drosophila genes, san (separation anxiety) and deco (Drosophila eco1), disrupt centromeric sister chromatid cohesion very early in division. This failure of sister chromatid cohesion does not require separase and is correlated with a failure of the cohesin component Scc1 to accumulate in centromeric regions. It thus appears that these mutations interfere with the establishment of centromeric sister chromatid cohesion. Secondary consequences of these mutations include activation of the spindle checkpoint, causing metaphase delay or arrest. Some cells eventually escape the block but incur many errors in anaphase chromosome segregation. Both san and deco are predicted to encode acetyltransferases, which transfer acetyl groups either to internal lysine residues or to the N terminus of other proteins. The San protein is itself acetylated, and it associates with the Nat1 and Ard1 subunits of the NatA acetyltransferase.At least two diverse acetyltransferases play vital roles in regulating sister chromatid cohesion during Drosophila mitosis.